Idiopathic Neonatal Colonic Perforation - Nihat Demir; Oğuz Tuncer; Mehmet Melek; Sultan Kaba; Keziban Bulan; Erdal Peker (EL-Med-Pub, 2014)
Though the perforation of the colon in neonates is rare, it is associated with more than 50% mortality in high-risk patients. We report a case of idiopathic neonatal perforation of the sigmoid colon in an 8-day-old, healthy, male neonate without any demonstrable cause.